Single-sided magnetic particle imaging using perimag magnetic nanoparticles - Noordin Asimi, Mohd Noor; S, Salim; M.M.A, Jamil; A.A., Sadiq; N.A.A, Rahman; N, Othman (2019)
This paper presents the design of a simple, low cost single-sided magnetic particle imaging (MPI) scanner with Perimag magnetic nanoparticles employed as tracer material. The electromagnetic coils of the developed scanner were designed in the form of the solenoid to combat the cost and sensitivity limitation of the Helmholtz coil arrangement which reduces the image resolution. Liquid and immobilised Perimag nanoparticles samples were exposed to the superimposed magnetic field generated by the excitation and selection field coils at the field-free point. The nanoparticles (MNPs) responded with a non-linear magnetization, which is recorded in the form of a voltage signal by a gradiometer pickup coil. The second-harmonic component of the recorded signal is extracted by a resonant circuit and logged into the computer. Contour images of the MNPs distribution were obtained via solving the ill-posed image reconstruction equation using the Kaczmarz method, with the system matrix determined using model-based approach. The contour maps for one sample imaging revealed the position, shape, and size of the Perimag MNPs samples in the XY-plane at distance of 10 mm, 20 mm, 25 mm and 30 mm under the pickup coil. However, the results of two samples imaging indicated constructive interference effects, as the two samples cannot be distinguished at 20 mm below the pickup coil. The developed scanner has a spatial resolution of less than 1 mm and 42.1 ms image acquisition time. Thus, the outcome of this research showed that the developed single-side MPI scanner has a potential in the detection of MNPs, which could help in sentinel lymph node biopsy (SLNB) for breast cancer diagnosis